Affirmative action through minority reserves: an experimental study on school choice - Klijn, Flip (2022)
Minority reserves are an affirmative action policy proposed by Hafalir et al. (2013) in the context of school choice. In a laboratory experiment, we find that adding minority reserves to the GS and TTC mechanisms has positive effects on stability but is quite disappointing in terms of efficiency. Also GS induces higher rates of truth-telling by minority students and thus outclasses TTC